The role of L1 in L2 classes - Luluk Iswati; Arum Octaviani Hadimulyono (Universitas Islam Sultan Agung, 2018)
The use of L1 in L2 classes has long been a controversy. Krashen (1981) proposes that to succeed in L2 learning, L2 should be exposed extensively. Furthemore, he asserts that failure in L2 exposure is caused by available access to use L1. In contrast with Krashen’s theory, numerous researchers point out that the use of L1 in L2 classess turns out to be beneficial. According to Cook (2001) and Tang (2002), L2 learning and comprehension increase when L1 is used. This research aimed to reveal the role of L1 (Bahasa Indonesia) by both teachers and learners in English classrooms at tertiary level. The data were obtained from questionnaires distributed to 158 students and 23 teachers at a private university in Yogyakarta. Interviews were also conducted to 5 teachers. The findings show that 59% students and 70% teachers stated that L1 should be used in their class. 87% students stated that L1 should be used during explanation of difficult concepts of L2, and this is in line with 96% teachers who admitted that they use L1 when explaining difficult concepts. 40% students and 61% teachers were quite certain that using L1 in an English class helps learners ‘ learning process. L1 use is also contributive in lowering learners’ affective filter as it will make them more secure, comfortable, and eventually confident to use the target language. The overall findings suggest that L1 should be used in L2 classess, since its absence may hinder learners’ learning process.